Superselective Ophthalmic Artery Thrombolytic Therapy for Hyaluronic Acid Embolization: A Case Report - Wu Q; Fu Q; Xu X; Zheng C; Zhang J; Chen M (Dove Medical Press, 2022)
Qian Wu,1,* Qiang Fu,1,* Xiao Xu,2 Can Zheng,1 Jie Zhang,3 Minliang Chen1 1Department of Plastic and Reconstructive Surgery, Senior Department of Burns and Plastic Surgery, The Fourth Medical Center of Chinese PLA General Hospital, Beijing, People's Republic of China; 2Department of Ophthalmology, The Third Medical Center of Chinese PLA General Hospital, Beijing, People's Republic of China; 3Department of Interventional, The Fourth Medical Center of Chinese PLA General Hospital, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Minliang Chen, Department of Plastic and Reconstructive Surgery, Senior Department of Burns and Plastic Surgery, The Fourth Medical Center of Chinese PLA General Hospital, No. 51 Fucheng Road, Haidian District, Beijing, 10048, People's Republic of China, Tel +86 13911138381, Email chenml@sohu.com Xiao Xu, Department of Ophthalmology, The Third Medical Center of Chinese PLA General Hospital, No. 69 Yongding Road, Haidian District, Beijing, 100039, People's Republic of China, Tel +86 13381020161, Email 13623345@qq.comAbstract: Blindness caused by embolization of fillers is a rare but catastrophic complication after cosmetic injection. Vision improvement is rarely reported among the various studies on potential clinical treatments. In this case, the patient suffered from ophthalmic artery occlusion with no light perception 48 h after hyaluronic acid injection. After two intra-arterial thrombolytic therapy sessions and traditional sequential therapy, ocular appearance was restored to normal, blood supply to the retina and visual function were improved, and visual acuity was restored to hand motion levels. Our results suggest that intra-arterial thrombolytic therapy with hyaluronidase and papaverine has a positive effect on hyaluronic acid-induced visual loss and is worthy of clinical promotion.Keywords: complication, filler embolism, intra-arterial thrombolytic therapy, visual function